Climate Policies after Paris: Pledge, Trade, and Recycle - Christoph Böhringer; Sonja Peterson; Thomas F. Rutherford; Jan Schneider; Malte Winkler (ZBW - Leibniz Information Centre for Economics, 2021)
This article summarizes the insights of an Energy Modeling Forum study on the magnitude and distribution of economic adjustment costs to greenhouse gas emission constraints in the aftermath of the Paris Agreement where countries voluntarily committed themselves to Nationally Determined Contributions (NDCs). The model cross-comparison suggests that tightening of NDCs in line with the commonly agreed 2◦C temperature target will induce global economic costs of roughly 1% in 2030 - yet, these cost are unevenly spread across regions with fossil fuel exporting countries being most adversely affected from the transition towards a low-carbon economy. In order to reduce adjustment costs at the global and regional level, comprehensive emissions trading which exploits least-cost abatement options is strongly desirable as it can relax contentious normative debates on equitable burden sharing. Lump-sum recycling of revenues from GHG pricing in equal amounts to every household appeals as an attractive strategy to mitigate regressive effects of emission pricing and thereby make stringent climate policy more acceptable on societal fairness grounds.
Keywords: D58; H23; Q54; Q58; 330; Paris Agreement; emissions pricing and trading; revenue recycling